IDENTITY ISSUE IN POSTMODERN CONDITIONS - Abysova, Maria (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2024)
Introduction. The issue of identity research is crucial in the postmodern world, as it allows for the realization of any subjectivity. It’s therefore essential to find common grounds for socially acceptable forms of identification and the communicative forms that support them. The aim is the analysis of communicative practices of identity formation and maintenance practices in postmodern social reality. The tasks are 1) consider the specifics of identity as an integral quality of an individual based on leading approaches in socio-philosophical knowledge; 2) to investigate communicative practices of identity formation and maintenance in postmodern society. Research methods for the study are historical-philosophical method, systematic approach, dialectical method; theories of structuralism and poststructuralism; discursive and narrative approaches. Research results. The concept of identity is considered through the prism of the constructivist approach. Within the methodology of discursive and narrative approaches, constructivist opportunities at the social and individual levels of forming and maintaining self-identity are discussed, respectively. Discursive and narrative approaches appear as mutually complementary in studying the context of communicative situations and processes of individual assimilation of sociocultural experience in which identities are constructed and emerge. Discussion. In the unstable postmodern world, which is rapidly changing, the search for identity is carried out through communicative relations. Conclusions. Postmodern sociality is analyzed as a non-linear social dynamic that problematizes the maintenance of the basis of identity laid in historical experience and affirms the variety of projective identities. The postmodern situation actualizes the search for the practical synthesis of essentialism and constructivism.